Expressionism, Futurism, and the Dream of Mass Democracy - Douglas Brent McBride (Studies in 20th & 21st Century Literature, 2006)
This essay throws new light on a radical tendency in cultural modernism by analyzing the role of a single metaphor—the figure of politics as a stage—in political debates among German Expressionists and Italian Futurists before World War I. As the essay argues, this trope was used to critique liberalism's limited notion of popular rule and envision how disenfranchised masses might develop the political subjectivity needed to create a truly mass democracy. While the essay demonstrates that Futurists and Expressionists failed to develop a clear vision of what form mass democracy might take, it concludes that they agreed on one point. It would have to entail a qualitative transformation of the democratic ideal of popular sovereignty, rather than a quantitative extension of voting rights. This conclusion throws new light on the political character of cultural modernism before 1914. Whereas recent research has focused on proto-fascist tendencies in modernist ideology, this analysis shows that Expressionism and Futurism initially shared a commitment to the democratic ideal of popular sovereignty that was incommensurable with fascist methods of orchestrating popular consent for authoritarian rule.
Keywords: Expressionism; futurism; mass democracy; cultural modernism; politics; stage; politics as a stage; metaphor; German Expressionists; Italian Futurists; World War I; trope; liberalism; popular rule; disenfranchised masses; disenfranchize; qualitative transformation; transformation; before 1914; proto-fascist; modernist ideology; authoritarian rule